The impact of cultural dimensions on online store loyalty - Dikčius, Vytautas; Adomavičiūtė-Sakalauskė, Karina; Kiršė, Sigita; Zimaitis, Ignas (Journal of Business Economics and Management, 2023)
Although online stores operate internationally for an already long time, the impact of cultural differences on them only recently gained interest. The aim of this study is to assess the impact of cultural dimensions on loyalty to online stores. It is based on a systematic analysis of 10 core databases that included 3,557 articles published between 2000 and 2020. Using PRISMA steps, 116 articles, totalling around 56,000 respondents from 25 different countries across all continents, are included in the meta-analysis. The results extend theoretical knowledge by showing that uncertainty avoidance harms customer loyalty, while masculinity has a positive impact. Additionally, it is found that loyalty is lower in countries with a low level of long-term orientation and higher in countries with a high level of power distance or a low level of indulgence. Lastly, individualism has no impact on the level of loyalty. Theoretical and managerial implications are also presented.